2018
DOI: 10.1074/jbc.ra118.004683
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-phase diagrams of β2-microglobulin reveal temperature and salt effects on competitive formation of amyloids versus amorphous aggregates

Abstract: Several serious diseases are associated with crystal-like amyloid fibrils or glass-like amorphous aggregates of denatured proteins. However, protein aggregation involving both types of aggregates has not yet been elucidated in much detail. Using a protein associated with dialysis-related amyloidosis, β-microglobulin (β2m), we previously demonstrated that amyloid fibrils and amorphous aggregates form competitively depending on salt (NaCl) concentration. To examine the generality of the underlying competitive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…2 and SI Appendix, Fig. S1 B and C), we observed a rapid increase in LS followed by a delayed increase in ThT fluorescence after a lag time, indicating kinetic competition between rapid amorphous aggregation or oligomer formation and the slow conversion to amyloid fibrils, as predicted by the competitive mechanism of amorphous aggregation and amyloid formation (1,2,5,11). However, we have no structural or morphological evidence for transient amorphous aggregation, and further studies are required to verify this.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…2 and SI Appendix, Fig. S1 B and C), we observed a rapid increase in LS followed by a delayed increase in ThT fluorescence after a lag time, indicating kinetic competition between rapid amorphous aggregation or oligomer formation and the slow conversion to amyloid fibrils, as predicted by the competitive mechanism of amorphous aggregation and amyloid formation (1,2,5,11). However, we have no structural or morphological evidence for transient amorphous aggregation, and further studies are required to verify this.…”
Section: Resultsmentioning
confidence: 70%
“…LS intensity gradually increased and exceeded the detection limit at 2 M orthoP, at which amorphous aggregates dominated. Previous studies showed that although low concentrations of NaCl produced amyloid fibrils, high concentrations of NaCl (e.g., 1.0 M) produced amorphous aggregates, making an optimum for amyloid formation at ∼0.2 M NaCl (1,2,5,12). Thus, the effects of orthoP on amyloid formation are similar to those of NaCl, although amyloid fibrils remained even at 1 M orthoP.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations